1964
DOI: 10.2466/pms.1964.18.1.239
|View full text |Cite
|
Sign up to set email alerts
|

Visual Apparent Movement Research: Review, 1935–1955, and Bibliography, 1955–1963

Abstract: Publications from 1935 to 1955 on visual apparent movement are compiled, described and broadly classified by content to facilitate reference search. Since understanding of the basic processes in visual real movement is regarded as essential to the explanation of apparent movement, critical evaluation is minimal and studies of real movement are cited where pertinent. A supplementary appendix provides references covering the period of 1955 to 1963 organized to correspond with text sections that describe the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1965
1965
1989
1989

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 149 publications
0
5
0
Order By: Relevance
“…Moreover, it was also pointed out that the time element, in the form of intermittency and repetition, appears to facilitate multisensory integration (Schiller, 1935;Zietz & Werner, 1928). The study of apparent movement has been carried out most thoroughly in the visual modality (Aarons, 1964;Graham, 1965;Kolers, 1972;Neuhaus, 1930;Wertheimer, 1912), but the phenomenon has also been observed in the auditory (Briggs & Perrott, 1972;Burt, 1917) and haptic (Sherrick & Rogers, 1966) modalities as well. Hereupon, the intersensory relation among these apparent movements became a center of attention.…”
mentioning
confidence: 99%
“…Moreover, it was also pointed out that the time element, in the form of intermittency and repetition, appears to facilitate multisensory integration (Schiller, 1935;Zietz & Werner, 1928). The study of apparent movement has been carried out most thoroughly in the visual modality (Aarons, 1964;Graham, 1965;Kolers, 1972;Neuhaus, 1930;Wertheimer, 1912), but the phenomenon has also been observed in the auditory (Briggs & Perrott, 1972;Burt, 1917) and haptic (Sherrick & Rogers, 1966) modalities as well. Hereupon, the intersensory relation among these apparent movements became a center of attention.…”
mentioning
confidence: 99%
“…The mechanism of directional detection is unknown, although directional specific cells have been found in the pigeon retinae (Maturana and Frenk, 1963) and the optic tectum (Wylie, 1962). While it has been speculated that perception of real movement and apparent movement are derived from the same basic electrophysiological process (Aarons, 1964), thus far the two have been shown to be behaviorally equivalent only in the cat (Smith, 1937). The present study with pigeons was designed to assess stimulus generalization between real and apparent movement on the dimension of direction.…”
mentioning
confidence: 99%
“…In 1875 Exner reported that when a spot of light is presented first in one position and, after an appropriate time interval, again in a second position, observers perceive the spot to translate through the shortest path connecting its successive positions (cf Boring 1942). A number of later studies (reviewed by Neff 1936;Aarons 1964;Kolers 1972) have further explored the spatiotemporal conditions for the perception of apparent continuous translation.…”
Section: Introductionmentioning
confidence: 99%